How damaging is part-time employment to a woman's occupational prospects? - Victoria Prowse (Institute for the Study of Labor (IZA), 2005)
This paper investigates the causes of the well documented association between part-time employment and low occupational attainment amongst British women. In particular, the relative importance of structural factors and unobserved heterogeneity to the occupational attainment of women who choose to work part-time is investigated. The results indicate that there are significant structural impediments to women in part-time employment obtaining their true occupational potential. However, structural factors explain only part of the relatively low occupational attainment of women in part-time employment: differences in unobserved characteristics between part-time and full-time workers also contribute to the low occupational attainment of women in part-time employment.
Keywords: C15; C35; C23; J62; 330; dynamic labor supply; heterogeneity; occupational attainment; part-time employment